Why mental health matters to global health. (December 2014) - Patel, Vikram
Global health has been defined as an area of study, research, and practice that places a priority on improving health and achieving equity in health for all people worldwide. This article provides an overview of some central issues in global mental health in three parts. The first part demonstrates why mental health is relevant to global health by examining three key principles of global health: priority setting based on the burden of health problems, health inequalities and its global scope in particular in relation to the determinants and solutions for health problems. The second part considers and addresses the key critiques of global mental health: (a) that the "diagnoses" of mental disorders are not valid because there are no biological markers for these conditions; (b) that the strong association of social determinants undermines the use of biomedical interventions; (c) that the field is a proxy for the expansion of the pharmaceutical industry; and (d) that the actions of global mental health are equivalent to "medical imperialism" and it is a "psychiatric export." The final part discusses the opportunities for the field, piggybacking on the surge of interest in global health more broadly and on the growing acknowledgment of mental disorders as a key target for global health action.